The Correlation Between Tool Wear and Vibration Signals from Piezoelectric in End Milling of AISI P20+NI / Nurul Hidayah Md Tahir...[et al.] - Md Tahir, Nurul Hidayah; Rizal, Muhammad; Wan Mansor, Wan Nuha; A. Ghani, Jaharah; Nuawi, Mohd Zaki; Che Haron, Che Hassan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This paper presents, the relationship between the flank wear of a carbide cutting tool and the vibration signal under various cutting conditions during the end milling of AISI P20. AISI P20 steels are typically used for making plastic injection mold, die extrusion, blow molding and various other components. The tests were conducted under various combinations of the cutting speed (200 and 300 m/min) and feed rate (0.1 and 0.2 mm/tooth), whilst the depth of cut is kept constant at 1 mm. The vibrations due to the flank wear were measured using piezoelectric sensors embedded within an integrated rotating dynamometer. The amplitude of the vibrations increased with increasing flank wear. The experimental results showed that the amplitude of the vibration signals increased due to the progression of the flank wear as well as with an increase as the cutting speed.